Liuzijue Qigong: A Voice Training Method For Unilateral Vocal Fold Paralysis Patients. (July 2019) - Tang, Jun; Huang, Wei; Chen, Xuhui; Lin, Qian; Wang, Tingwei; Jiang, Hao; Wan, Ping; Huang, Zhaoming
Objectives: Liuzijue Qigong (LQG), a kind of traditional Chinese health exercise (TCHE), is not only widely used to strengthen physical fitness and maintain psychological well-being in the elderly but has also been utilized to help improve respiratory function. As respiratory support is an important driving force for speech production, it is logical to postulate that the LQG training method with 6 monosyllabic speech sounds, xū, hē, hū, sī, chuī, and xī, can help individuals (1) experience a relaxing and natural state of speech production, (2) eliminate voice symptoms, and (3) improve their overall body function and mood. In the current study, we hypothesized that the LQG method with these 6 sounds can be effective in improving vocal function in subjects with unilateral vocal fold paralysis (UVFP) in comparison with a conventional voice therapy method. Methods: A total of 48 patients with UVFP who met the inclusion criteria were randomly divided into 2 groups. Twenty-four subjects in the experimental group were trained with LQG, and those in the control group received conventional voice training (abdominal breathing and yawn-sign exercises) for a total of 4 sessions, twice a week. Patients in both groups were assessed with acoustic tests, the GRBAS scale, the Voice Handicap Index (VHI-10), and the Hospital Anxiety and Depression Scale (HADS) pre- and posttreatment. Statistical analysis was conducted using nonparametric tests and t tests. Results: There existed significant changes in maximum phonation time (MPT), jitter, shimmer, normalized noise energy (NNE), GRBAS scores, VHI-10 scores, and grade of A in HADS scores pre- and posttreatment in both the experimental group and the control group ( P < .004). However, no significant changes were seen posttreatment between the 2 groups ( P > .05). Conclusions: LQG could help improve vocal function in UVFP patients as our preliminary data showed no significant differences between LQG and conventional voice therapy methods.